Double gene targeting multiplex PCR-RFLP detects Crocodylus porosus in chicken meatball and traditional medicine - Ahmad Nizar, Nina Naquiah; Sultana, Sharmin; Hossain, M.A. Motalib; Johan, Mohd Rafie; Ali, Md. Eaqub (Taylor & Francis, 2018)
Crocodiles have been hunted and consumed for centuries for skins, nutrients, and medicines. These indomitable trends have overpowered restrictions from wildlife and conservation agencies, continuing the illegal trades of crocodiles across the world. This paper described the development of a very stable, fast, and secured polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay for the confirmed detection of Crocodylus porosus under any matrices and decomposing treatments. Two very short-sites (77 and 127-bp) of atp6 and cytb genes of C. porosus were controlled digested with AciI enzyme; producing distinctive RFLP patterns (83, 54, 44 & 23 bp). The enzyme digested assay was stable following extreme boiling, autoclaving, and microwaving treatments that break down DNA. The sensitivity was tested and validated in model meatballs and it was suitable for detecting 0.01% crocodile meatball matrices. The optimized RFLP assay was used to screen 3 commercial meatballs and 21 traditional medicines (TM). While no crocodile DNA was found in commercial chicken meatballs, 4/21 TM products were found correctly labelled to contain C. porosus DNA. The novel assay demonstrated sufficient merit to be used by regulatory agencies for any forensic and/or archaeological identification of C. porosus even under the state of decomposition.